6(y-9)=4(y-5)

Simple and best practice solution for 6(y-9)=4(y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y-9)=4(y-5) equation:


Simplifying
6(y + -9) = 4(y + -5)

Reorder the terms:
6(-9 + y) = 4(y + -5)
(-9 * 6 + y * 6) = 4(y + -5)
(-54 + 6y) = 4(y + -5)

Reorder the terms:
-54 + 6y = 4(-5 + y)
-54 + 6y = (-5 * 4 + y * 4)
-54 + 6y = (-20 + 4y)

Solving
-54 + 6y = -20 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
-54 + 6y + -4y = -20 + 4y + -4y

Combine like terms: 6y + -4y = 2y
-54 + 2y = -20 + 4y + -4y

Combine like terms: 4y + -4y = 0
-54 + 2y = -20 + 0
-54 + 2y = -20

Add '54' to each side of the equation.
-54 + 54 + 2y = -20 + 54

Combine like terms: -54 + 54 = 0
0 + 2y = -20 + 54
2y = -20 + 54

Combine like terms: -20 + 54 = 34
2y = 34

Divide each side by '2'.
y = 17

Simplifying
y = 17

See similar equations:

| 2xsquared+5x+4=0 | | 7q+14=5(2q)-55 | | (16b-2)-5(3b+3)=-4 | | sqrt(8-x)+4-sqrt(4x-3)=0 | | (3x+2)(2x-1)=0 | | 10x-15=25-2x | | 5x+7=6+3x+1+2x | | ln(8-9x)=-1 | | ln(9x+8)=-1 | | -6q+72=q+269 | | 2(3+w)=41 | | 30x+5=125 | | 13p+3=p-597 | | x+(x+2)=108 | | 5(2x-4)=3(3x+6) | | (3(x-5a+9))= | | 5/3*2= | | x+12=4x-6 | | 20+1.25d=2.5d | | 5x-15x-7=5(4x+4) | | 8-n=1+2n-2n | | v+162=-4v-3 | | .04x+x=5200000 | | 117x^2+8xy+117y^2-484x-484y=12705 | | 6+x=26 | | b+84=-5b-6 | | -5-(15y-1)=2(7x-16)-x | | -4(-4+7x)=-152 | | 2x+2y+6=(x)(y)+3 | | (.01)(1-x)+(.063)(x)=(.02)(1) | | .04x+x=5300000 | | 58x+44=160 |

Equations solver categories